Abiotic variables influencing the nocturnal movements of bobcats and coyotes. Issue 3 (8th July 2020) - Melville, Haemish I. A. S.; Conway, Warren C.; Hardin, Jason B.; Comer, Christopher E.; Morrison, Michael L.
Abstract : Despite the increasing spatial, temporal and dietary overlap between bobcats Lynx rufus and coyotes Canis latrans, these species live sympatrically throughout much of North America. To determine if differential activity patterns relative to abiotic variables might influence interspecific interactions, we investigated whether these species responded differentially to crepuscular and nocturnal abiotic variables in Texas. Using GPS collars, we calculated hourly movements from sequential locations, and compared bobcat and coyote movements relative to sex, season, moonlight intensity, night period, crepuscularity and temperature. We used generalized linear mixed effects models (GLMM) to investigate the responses of bobcats and coyotes to variables associated to their nocturnal movements. Temperature and its interactions with various abiotic variables influenced bobcat movements. Biological season and its interactions with other abiotic variables influenced coyote movements. Bobcats moved shorter hourly distances than coyotes. Female bobcats moved shorter hourly distances than males. Moonlight intensity seemed to influence coyotes but not bobcats. Differential movements between bobcats and coyotes relative to night period could possibly be due behavioral avoidance of coyotes by bobcats. Reduced crepuscular activity by coyotes may be behavioral avoidance of humans. Differential responses to nocturnal variables may dampen competitive interactions between bobcats and coyotes.